2020
DOI: 10.1038/s41598-020-72486-6
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) and transgender identity: new original data and a meta-analysis

Abstract: Previously reported associations between second-to-fourth digit length ratio (2D:4D), a proxy for prenatal androgen load, and transgender identity have been inconsistent. The objectives of the present study were to provide additional original data and an updated meta-analysis concerning this association. In a study of 464 participants, we compared the 2D:4D of transgender individuals with age- and sex-matched controls. Patients were recruited at a specialized psychiatrist’s medical office, whereas controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 81 publications
1
15
1
Order By: Relevance
“…First, contrary to the prediction that more masculine groups would show lower 2D:4D, toms had higher left 2D:4D than lesbian women. That said, lack of support for our prediction is not necessarily out of step with other literature given recent meta-analytic findings suggesting no differences in 2D:4D between heterosexual women and trans men 16 . As such, processes contributing to digit ratio might not be related to the development of masculine identity among individuals assigned female at birth.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…First, contrary to the prediction that more masculine groups would show lower 2D:4D, toms had higher left 2D:4D than lesbian women. That said, lack of support for our prediction is not necessarily out of step with other literature given recent meta-analytic findings suggesting no differences in 2D:4D between heterosexual women and trans men 16 . As such, processes contributing to digit ratio might not be related to the development of masculine identity among individuals assigned female at birth.…”
Section: Discussioncontrasting
confidence: 66%
“…As such, this pattern runs contrary to a recent study that reported digit ratio was more female-typical among gay men who expressed feminine gender role behavior 57 . Further, meta-analyses have suggested digit ratio is more female-typical (vs. heterosexual men) among trans women 16 , but not gay men 12 (but see findings with an adolescent sample 58 ). Given the discrepant findings, it will be important for future research to continue to examine digit ratio in relation to both sexual orientation and gender identity/expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All factor loadings were ≥0.30 (median, 0.86; range, 0.34-0.96). The GIDYQ-AA has strong evidence for discriminant validity and a high threshold for specificity (i.e., low false positive rate for non-GID individuals) [see (95,96,(99)(100)(101)(102)].…”
Section: Concurrent Gender Identitymentioning
confidence: 99%
“…Both biological (Sadr et al, 2020;Siegmann et al, 2020) and psychosocial (Schnarrs et al, 2019) factors are involved in the etiology of GD. Structural magnetic resonance imaging tecniques highlighted neuroanatomical similarities between transgender and cisgender individuals sharing the same birthassigned sex (Khorashad et al, 2021), i.e.…”
Section: Introductionmentioning
confidence: 99%